2004
DOI: 10.1023/b:ddas.0000042248.48819.ad
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Lactulose on Dextran Sulfate Sodium-Induced Colonic Inflammation in Rats

Abstract: Promising results have recently been obtained with pre- and probiotic therapy in ulcerative colitis (UC). The prebiotic potential of lactulose is well established, but it has not yet been investigated in experimental colitis models. The purpose of the study was to examine the effect of lactulose on an UC model induced by 3% dextran sulfate sodium (DSS) solution added to drinking water for 7 days in male Wistar rats. Lactulose (300-1000 mg/kg) or 5-aminosalicylic acid (5-ASA; 150 mg/kg) was administered orally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…This finding supports other studies that have demonstrated that certain fermentable carbohydrates may protect against intestinal inflammation and reduce the symptoms of IBD patients [7,8,38]. Prebiotics are emerging as having important nutritional benefits in both healthy and disease states and further research into the mechanisms behind their actions are required to enable understanding of the full effects.…”
Section: Discussionsupporting
confidence: 87%
“…This finding supports other studies that have demonstrated that certain fermentable carbohydrates may protect against intestinal inflammation and reduce the symptoms of IBD patients [7,8,38]. Prebiotics are emerging as having important nutritional benefits in both healthy and disease states and further research into the mechanisms behind their actions are required to enable understanding of the full effects.…”
Section: Discussionsupporting
confidence: 87%
“…The DAI was determined macroscopically by an observer unaware of the treatment the mice had received according to previously reported criteria (34). Briefly, the DAI was calculated as the sum of the diarrheal stool score (0, normal stool; 1, mildly soft stool; 2, very soft stool; and 3, watery stool) and the bloody stool score (0, normal color stool; 1, brown color stool; 2, reddish color stool; and 3, bloody stool).…”
Section: Development Of Dss-induced Colitis and Measurement Of Colon mentioning
confidence: 99%
“…The amounts of TBARS in the colonic tissues were measured as described previously (35,38). After 7 days of DSS treatment, animals were placed under deep ether anesthesia and killed.…”
Section: Lipid Peroxidation Measured By Thiobarbituric Acid-reactive mentioning
confidence: 99%
“…19 Prebiotics are defined as Bnondigestible dietary supplements that have the ability to alter the intestinal flora and stimulate growth of native and probiotic bacteria.^2 0 Prebiotics, such as germinated barley foodstuff and lactulose, have been reported to decrease the severity of DSS-colitis. 21,22 In a clinical setting, inulin has been demonstrated to reduce the extent of inflammation in patients with pouchitis. 23 The prebiotic, fructooligosaccharide (FOS), is a nondigestible oligosaccharide with the capacity to increase intestinal concentrations of Lactobacilli and Bifidobacterium species.…”
mentioning
confidence: 99%